Growth and rhizome essential oil yield of camia (Hedychium coronarium Koenig) under varying shade levels and photoperiod - Rosas, M. L. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2004)
The effect of varying levels of shade and daylength on the vegetative and reproductive growth and rhizome essential oil yield of camia, Hedychlum coronarium Koenig, was examined. Camia plants were exposed to 0%, 38%, 59% and 75% levels of shade. Light duration treatments, on the other hand, were given by subjecting the plants to natural daylength, ND (11.9-h daylength); short day, SD (8-h daylength); long day, LD (16-h daylength) and continuous light, CL (24-h daylength). Shade levels significantly affected all growth parameters measured except for number of leaves, root length and stem dry weight. Plant height and total leaf area increased with increase in shade levels, while the leaf dry matter index, number of roots and weights of most of the plant organs were favored by open and up to 38% partial shade conditions. The essential off content of the rhizomes was not influenced by shade. In contrast, essential oil yield was highest when plants were grown in open conditions, and least in 75% shade. Light duration also modified the growth response of camia except for root length and leaf dry weight. Long-day exposures tended to produce taller plants while shorter photoperiods promoted the number of suckers and roots. The weight of roots and rhizomes were heaviest under MD, and of stems and fresh leaves under CL. Flowering in camia was induced only in LD and CL treatments. The number of days to flower initiation between the two long-day exposures was statistically similar. As with shade, light duration had no effect on essential oil content of the rhizomes. Essential oil yield was highest in plants subjected to ND, but it did not significantly vary among plants treated with SD, LD and CL.